Assessment of risk factors of inguinal hernia (Journal of Pharmaceutical Negative Results, 2022)
Background: Inguinal hernia repair is a commonly performed general surgery procedure in both adults and children with inguinal hernias constituting more than 95% of all groin hernia repairs. The present study was conducted to assess risk factors of inguinal hernia. Materials & Methods: 94 cases of inguinal hernia of both genders were enrolled. Parameters such as the type of hernia, primary or recurrent was noted. Period of swelling, side and risk factors were recorded. Results: Out of 94 patients, males were 60 and females were 34. Side was right in 28, left in 30 and bilateral in 36. Type of hernia was primary in 54 and recurrent in 40. Period of swelling was <1 year in 32, 1-2 years in 40 and >2 years in 22. The difference was significant (P< 0.05). Common risk factors for inguinal hernia were COPD in 24, lifting heavy objectsin 88, alcoholism in 26, smoking in 34, diabetes in 30, family history in 11, bowel disturbances in 72 and age >60 yearsin 26. The difference was significant (P< 0.05). Conclusion: Common risk factors for inguinal hernia were COPD, lifting heavy objects, age >60 years, alcoholism, smoking, diabetes, family history and bowel disturbances.